Difficulties and measures of driving super long piles in Bohai Gulf. Issue 2 (March 2015) - Yan, Shuwang; Li, Jia; Sun, Liqiang; Sun, Guomin
Abstract: Long piles of the ocean oil platform are usually manufactured as the integration of several segments, which have to be assembled one by one during installation. During pile driving, excessive pore pressure will build up in such a high level that hydraulic fracturing in the soil round the pile may take place, which will cause the soil to consolidate much faster during pile extension period. Consequently, after pile extension, the soil strength will recover to some extent and the driving resistance will increase considerably, which makes restarting driving the pile very difficult and even causes refusal. A finite element (FE) analysis procedure is presented for judging the risk of refusal by estimating the blow counts after pile extension, in which the regain of soil strength is considered. A case analysis in Bohai Gulf is performed using the proposed procedure to explain the pile refusal phenomenon.